STRUKTUR KOMUNITAS BURUNG DI TAMAN SITULEMBANG, TAMAN SUROPATI , DAN TAMAN MENTENG, JAKARTA PUSAT - Nugroho, Juliadi (LPPM Universitas Negeri Jakarta, 2016)
Birds are one of the animals that can be encountered utilizing City Park as a habitat. The existence of birds in a habitat influenced by factors such as life support shelter and feed availability. Situlembang Park, Suropati Park, and Menteng Park has a different characteristic. The purpose of this research was to observe differences in the structure of bird communities in the three parks. This study was conducted in January-March 2015 using descriptive method with point count technique. Results of the research the highest abundance of species in the Situlembang park is Pycnonoctus aurigaster, while bird species in Menteng Park and Suropati Park is Passer mountanus. The highest levels of bird diversity found in Situlembang park is 2,37 then Suropati Park (2.18), and Lowest Menteng Park (2.17). Bird species evenness index in the three parks is high (0.80 to 0.81) and and the dominance index is low (0.13 to 0.15) .The level in similarity index of bird species in the three parks is high (0,80- 0.88).